680 Peripheral intravascular lithotripsy of ILEO-femoral arteries to facilitate transfemoral TAVI: a multicentric prospective registry. (8th December 2021) - Nardi, Giulia; Backer, Ole De; Saia, Francesco; Sondergaard, Lars; Ristalli, Francesca; Meucci, Francesco; Stolcova, Miroslava; Mattesini, Alessio; Demola, Pierluigi; Wang, Christina Xi; Jabri, Anees Al; Bruno, Antonio Giulio; et al.
Abstract: Aims: The presence of severe calcific atherosclerosis at the iliofemoral axis may preclude transcatheter aortic valve implantation (TAVI) by transfemoral (TF) approach. Intravascular lithotripsy (IVL) is a novel technology that fractures intimal/medial calcium and increases vessel compliance allowing TF-TAVI in selected patients with peripheral artery disease (PAD). To report on the safety and efficacy of IVL-assisted TF-TAVI in an all-comers population. Methods and results: Clinical, imaging and procedural data on all consecutive patients treated by IVL-assisted TF-TAVI in six high-volume European centres (2018–2020) were collected in this prospective, real-world, multicentre registry. IVL-assisted TF-TAVI was performed in 108 patients, increasing from 2.4% to 6.5% of all TAVI in 2018 to 2020, respectively. The target lesion was most often localized at the common and/or external iliac artery (93.5% of cases; average TL-MLD 4.6 ± 0.9 mm with 318 degrees of calcium arc). Transfemoral aortic valve delivery was successful in 100% of cases; final procedural success in 98.2% (two conversion to cardiac open surgery for annular rupture and valve migration). Complications of the IVL-treated segments consisted of one perforation and three major dissections requiring stent implantation (two covered stents and two BMS). Access site related complication included three major bleedings. Three in-hospital deaths were recorded (2.8%, one failed surgical conversion after annular rupture, one cardiac arrest after initial valvuloplasty, one late hyperkalaemia in renal dysfunction). Conclusions: IVL-assisted TF-TAVI proved to be a safe and effective approach, which helps expanding the indications for TF-TAVI in patients with severe calcific PAD. Still, these patients maintain a higher than average incidence of peri-procedural complication.